The Influence of Service Quality and Eco-Friendly Housekeeping Practices on Hotel Guest Satisfaction (LACULTOUR: Journal of Language and Cultural Tourism, 2026)
The hospitality industry is increasingly meeting the demand for improved service quality while implementing eco-friendly practices. This study aims to examine the effect of housekeeping service quality and eco-friendly practices on hotel guest satisfaction. The method used was a quantitative survey with questionnaires distributed to 47 hotel guests staying at the Lamora Hotel in Surabaya. The collected data were analyzed using validity and reliability tests, classical assumptions, and multiple linear regression. The results showed that housekeeping service quality and the implementation of eco-friendly practices have a positive influence on guest satisfaction. Housekeeping service quality, including cleanliness, punctuality, and staff maintenance, and the implementation of eco-friendly practices such as waste management and energy efficiency, together create a satisfying stay experience for guests. This study makes a significant contribution to the understanding of the relationship between service quality and environmental desires in the hospitality industry. The findings suggest that hotels should focus on improving housekeeping service quality and implementing eco-friendly practices to enhance guest satisfaction and their competitiveness in the market.